Future climate projection under IPCC A1B scenario in the source region of Yellow River with complex topography using RegCM3. Issue 19 (10th October 2014) - Hui, Pinhong; Tang, Jianping; Wang, Shuyu; Wu, Jian; Kang, Yue
Abstract: Located on the Tibetan Plateau, the source region of Yellow River has experienced remarkable climate change over past a few decades, which affects the regional ecosystem, agricultural development, and water availability. In this paper, high‐resolution RegCM3 driven by ECHAM5 is applied to generate both control climate for 1980–2000 and regional climate projections for the 21 st century (2010–2098) under the Intergovernmental Panel on Climate Change (IPCC) A1B emission scenario. For control climate, RegCM3 can well reproduce the spatial patterns of precipitation and surface air temperature with more detailed representation of fine scale topography. Wet and cold biases are produced in the simulation, but overall improvement by RegCM3 is evident compared to the driving global climate model (GCM) of ECHAM5. In the future projection, the model demonstrates significant warming over the whole analysis domain. Precipitation on the other hand shows mixed signals of reduction and increase over simulation domain, while the areas of precipitation reduction extend with increasing integration time and finally cover most parts of the domain at the end of 21 st century. As projection time increases, high altitude region will experience more precipitation reduction in summer and less reduction or even increase in winter. The winter warming at the high elevation area gets more evident than that at the low elevation area, which may be due to the snow feedback. Analyzing the change of probability distributions of surface climate, it can be concluded that the frequency of heavy precipitation in winter tends to increase with time indicating more extreme precipitation events in the future. The spectrum of temperature probability density functions (PDFs) moves toward higher end. Key Points: High‐resolution RegCM3 is used to project climate in the YR Source Region The region would be more warming in the future especially at high altitude High altitude shows more rain reduction in JJA